Perbedaan Kadar Hemoglobin Pada Ibu Hamil Sebelum Dan Sesudah Pemberian Kurma - Hery Prambudi; Usdiyanto Usdiyanto; Solikhah Solikhah; Citania Nurkholifah (Universitas Muhamadiyah Manado, 2021)
Pregnancy can cause the body to be very susceptible to low hemoglobin levels, which during pregnancy require sufficient iron for the body. If the body loses iron, anemia will occur, because the body requires the intake of foods that contain iron. Anemia itself where the value of the hemoglobin level is less than the normal value or below the normal value. So if a pregnant woman has a hemoglobin level below the normal value, she will be prone to anemia. The risk of anemia during pregnancy can occur in the fetus because it can affect the growth and development of the fetus and baby, as well as babies born prematurely or with reduced body weight. Dates are a fruit which contains many benefits for the body, one of which is to prevent anemia. The content of the date palm itself contains nutrients for the body such as protein, vitamin A, vitamin C, thiamine, ribovalfin, nicotinic acid, and iron. To determine hemoglobin levels in pregnant women before and after giving dates. The research method used this time was preexperimental with a one-group pre-test post-test research design. While the examination using the cyanmethemoglobin method. The results of the study of hb levels before being given dates with an average result of 11.94 and after being given dates the average result was 12.65 which showed an increase in hb levels. Data analysis using the Paired Sample Test statistical test obtained the results of sig (2 tailed) of 0.207 or > 0.05. From the results of the statistical analysis of the Paired Sample Test, it can be said that Ho is accepted, which means that there is no significant effect on the administration of dates on hemoglobin levels before and after.